2005
DOI: 10.17221/4245-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lecithin emulsifier on the utilisation of nutrients and growth of piglets after weaning

Abstract: ABSTRACT:The influence of supplementation of a lecithin emulsifier (0.1%) to the feed mixture for piglets after weaning was studied. 16 piglets in the control group (C -without lecithin) and 16 piglets in an experimental (E) group were monitored in three replications in a 28-day experimental period. We observed higher digestibility of monitored nutrients in the experimental group (crude fat: C = 66.28 ± 12.11, E = 69.75 ± 9.85%, crude protein: C = 78.72 ± 5.47, E = 82.17 ± 2.23%, crude fibre: C = 56.70 ± 12.85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…The effect of dietary lecithin on animal performance has received considerable attention over the last few years (Danek et al, 2005;Li, Liu, Zhao, & Kim, 2017;Soares & Lopez-Bote, 2002). In agreement with previous reports, adding SL to sows diet did not affect feed intake, weight loss, and BW gain or backfat thickness (Bontempo et al, 2004; Means within a row with different superscripts differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The effect of dietary lecithin on animal performance has received considerable attention over the last few years (Danek et al, 2005;Li, Liu, Zhao, & Kim, 2017;Soares & Lopez-Bote, 2002). In agreement with previous reports, adding SL to sows diet did not affect feed intake, weight loss, and BW gain or backfat thickness (Bontempo et al, 2004; Means within a row with different superscripts differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 86%
“…Abbreviation: IgG, immunoglobulin G; IgA, immunoglobulin A; IgM, immunoglobulin M. Lauridsen & Danielsen, 2004). In several studies, lecithin has been shown to improve ADG of piglets (Danek et al, 2005). Moreover, Li et al (2014) reviewed that 1% or 2% or 4% SL added in diets could significantly improve weight gain and final BW compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danek et al . [ 28 ] suggested that dietary supplementation of lecithin at 0.1% level along with fat (1.3%) showed 4-9% improvement in total feed intake than the non-supplemented group. Several authors [ 7 , 21 , 29 ] reported that animal fat was found to be less digestible in young pigs compared to fats of vegetable origin.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this result, Gheisar et al (2015) reported that the addition of lysolecithin and SSL to diets improved the digestibility of energy and nitrogen. Danek et al (2005) noted that supplementation of a lecithin emulsifier (0.1%) in the feed mixture for piglets after weaning improved the digestibility of crude fat. Neto et al (2011) suggested that broilers fed a diet with poultry offal fat and supplemented with an emulsifier showed higher digestibility of EE.…”
Section: Apparent Total Tract Digestibility Of Nutrientsmentioning
confidence: 99%